2016
DOI: 10.1164/rccm.201601-0099oc
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Airway Collapsibility and Loop Gain Predict the Response to Oral Appliance Therapy in Patients with Obstructive Sleep Apnea

Abstract: Our findings suggest that OA therapy improves the upper-airway collapsibility under passive and active conditions. Importantly, a greater response to therapy occurred in those patients with a mild anatomic compromise and a lower loop gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
160
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(177 citation statements)
references
References 41 publications
12
160
2
3
Order By: Relevance
“…In these patients, it is the presence of an elevated LG and/or low arousal threshold that is the primary effect modifier predisposing them to OSA. 12 Previous work has demonstrated that other CPAP alternative treatments such as mandibular advancement devices (MADs) and lateral positioning during sleep improve upper airway collapsibility without improving ventilatory control instability or arousal threshold, 13,14 such that these residual causes of OSA can persist despite intervention. While previous evidence suggests that upper airway surgery can improve the anatomy/collapsibility, [15][16][17] it also remains unclear whether upper airway surgery alters the nonanatomical factors that contribute to OSA.…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, it is the presence of an elevated LG and/or low arousal threshold that is the primary effect modifier predisposing them to OSA. 12 Previous work has demonstrated that other CPAP alternative treatments such as mandibular advancement devices (MADs) and lateral positioning during sleep improve upper airway collapsibility without improving ventilatory control instability or arousal threshold, 13,14 such that these residual causes of OSA can persist despite intervention. While previous evidence suggests that upper airway surgery can improve the anatomy/collapsibility, [15][16][17] it also remains unclear whether upper airway surgery alters the nonanatomical factors that contribute to OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, however, the choice of personalized treatment other than nCPAP for Patient A would be different than for Patient B. Patient A would likely benefit most from oral appliance therapy whereas Patient B may be better served by a pharmacologic intervention to lower loop gain and arousal threshold 10, 16, 17 . Also importantly, swapping therapy between patients would be particularly ineffective (e.g., Patient A instead receiving a pharmacologic intervention to lower loop gain and arousal threshold, and Patient B receiving oral appliance therapy), as the interventions would not target the primary causative factor in those individuals.…”
Section: Phenotyping Osa Patients Is Critical To Targeted Therapymentioning
confidence: 99%
“…The findings of that study indicate that non-anatomic factors are important and may be even more important than anatomic features in some patients, although a prime predisposing factor in most patients with OSA is a highly collapsible airway. A study based on this concept recently showed that OA improved upper airway collapsibility without affecting muscle function, loop gain, or the arousal threshold (Edwards et al 2016). This suggests that patients with better passive upper airway anatomy/collapsibility and low loop gain will obtain the greatest benefit from OA therapy (Edwards et al 2016).…”
Section: Predictors Of Treatment Successmentioning
confidence: 99%
“…A study based on this concept recently showed that OA improved upper airway collapsibility without affecting muscle function, loop gain, or the arousal threshold (Edwards et al 2016). This suggests that patients with better passive upper airway anatomy/collapsibility and low loop gain will obtain the greatest benefit from OA therapy (Edwards et al 2016). Gray et al (2016) reported that non-obese patients with OSA were more likely to have a low respiratory arousal threshold and that these patients were difficult to treat with CPAP.…”
Section: Predictors Of Treatment Successmentioning
confidence: 99%